2017
DOI: 10.3892/etm.2017.4312
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 PB balance and CD200 expression of patients with active severe alopecia areata

Abstract: Th1/Th2 peripheral blood balance and CD200 expression in patients with severe alopecia areata (SAA) in the active stage were investigated. Fifty patients with active SAA, 50 patients with stable SAA and 50 healthy controls were continuously selected and expression of Th1/Th2 of peripheral T lymphocytes, and peripheral B lymphocytes was detected by flow cytometry; RT-PCR was used to detect the expression of the PBMC CD200 mRNA and the expression of CD200 in hair follicles of alopecia area was detected by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…CD19 and CD200 are both expressed on immature and naïve B lymphocytes ( Rasmussen et al, 2015 ). This double staining has never been associated with MS, but a reduction in the number of CD19/CD200 B lymphocytes has recently been described in the acute phase of severe alopecia areata, a hair follicle-specific Th1 cell-mediated autoimmune disease ( Gilhar and Kalish, 2006 ; Ma et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD19 and CD200 are both expressed on immature and naïve B lymphocytes ( Rasmussen et al, 2015 ). This double staining has never been associated with MS, but a reduction in the number of CD19/CD200 B lymphocytes has recently been described in the acute phase of severe alopecia areata, a hair follicle-specific Th1 cell-mediated autoimmune disease ( Gilhar and Kalish, 2006 ; Ma et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of IL-10 in the serum of healthy subjects were higher than AA patients, but the difference was not significant (SMD = -0.22, 95% CI -0.95 to 0.50). Among six studies that report IL-10 levels in the sera of AA patients, one study shows reduced levels of IL-10 in AA patients compared to healthy controls 17 , one study shows a raised level 16 , and four studies show no significant difference 14,18,25, 26 . There was a significant elevation of IL-6 in the serum of AA patients compared to healthy controls (SMD = 1.57, 95% CI 0.17 to 2.97).…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies on the serum levels of these two inflammatory cytokines in AA patients have shown contradictory results 11,14, 15 . Furthermore, recent studies on the serum levels of IL-10 in AA patients have shown paradoxical results, including both in-creasing and decreasing 16, 17 . Several studies have explored the links between AA and IL-6, IL-10 and AA and TNF-α 11,16, 18 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the majority of previously published studies, an increased serum level of IFN-γ was observed in patients with alopecia areata compared to healthy controls [ 22 , 23 , 25 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Higher IFN-γ expression was also detected in peripheral blood mononuclear cells in patients with alopecia areata in comparison with the control group [ 42 , 43 ].…”
Section: Cytokines In Alopecia Areatamentioning
confidence: 99%